Factors Affecting Consumer Trust And Loyalty In Calysta Skincare Products At Branch Bumi Serpong Damai (BSD) - Heldy Aria Agusseta; Sylvia Sari Rosalina; Eko Sambodo (LPPM Universitas Respati Indonesia, 2024)
Claysta Skincare Clinic is competing to provide the best for its customers by giving more value to the clinic that differentiates it from the same competitors in the business business of Skincare clinics. Effect of product quality on Calysta Consumer confidence. Effect of product quality on Calysta Consumer loyalty, influence of service on Calysta Consumer trust, Effect of service on Calysta Consumer loyalty, price effect on Calysta Consumer trust, price effect on Calysta Consumer loyalty, influence of distribution on Calysta Consumer trust, influence of distribution on Consumer loyalty Calysta, the influence of brand image on Calysta Consumer trust, influence of brand image on Calysta Consumer loyalty, influence of consumer confidence on Calysta Consumer loyalty. Population in 80 consumers living in the Tangerang area who visited the Calyta Skincare Clinic in BSD Branch. Data collection techniques were obtained by distributing questionnaires. The data is analyzed by validity and reliability tests. The data analysis tool used in this study is Generalized Structure Component Analysis (GSCA). The results of this study indicate that product quality is not significantly positive effect on consumer trust, product quality is not significantly positive effect on customer loyalty, service has a significant positive effect on consumer trust, service has no significant positive effect on customer loyalty, price does not have a significant positive effect on consumer trust , price does not have a significant positive effect on consumer loyalty, distribution does not have a significant positive effect on consumer trust, distribution has a significant positive effect on customer loyalty, brand image has a negative significant effect on consumer trust, brand image has no significant negative effect on consumer loyalty, consumer trust no significant negative effect on consumer loyalty. Keywords: Trust, Consumer Loyalty, Product Quality, Service, Price, Distribution, Brand Image